Extraction and evolution of grader’s bionic morphological feature line using shape structure behavior function model - Qi, Bin; Lan, Yubin; Sun, Xiaoming; Zhu, He; Li, Yanhao; Lou, Ke (International Journal of Agricultural and Biological Engineering, 2024)
To improve the innovation of agricultural machinery product styling, this paper proposes a shape structure behaviorfunction (SSBF) model suitable for the industrial design field. The feature line evolution method combining shape grammar andgenetic algorithm was used for modelling the of the grader, which not only maintains the product style characteristics but alsoreflects the typical identification characteristics of the bionic prototype and produces a new product modelling scheme. Byconducting cognitive and recognition experiments on product styling features, the ranking of product styling features and thecontribution of each component to product styling were determined. The method of combining shape grammar and quadraticBézier curve was used to express and encode feature lines, and genetic algorithm was used to evolve biomimetic forms to formproduct feature lines with typical biological morphological features; The extracted form bionic elements were integrated intothe grader modelling design, and the interaction evaluation was carried out through the genetic algorithm evolution scheme.The basic form elements were extracted and analyzed, and the deduction rules were formulated and reorganized. The derivedfeature line geometric data considered the product’s image features and the bio-inspired prototype, which can be used for thefollow-up guidance of industrial design schemes.Keywords: bionic design, shape-structure-behavior-function, SSBF, biologically inspired design, BID, shape grammars,Quadratic Bézier curvesDOI: 10.25165/j.ijabe.20241702.8345Citation: Qi B, Lan Y B, Sun X M, Zhu H, Li Y H, Lou K. Extraction and evolution of grader’s bionic morphological featureline using shape structure behavior function model. Int J Agric & Biol Eng, 2024; 17(2): 74–84.